Finite difference time domain analysis of extended composite right/left‐handed transmission line equations. Issue 1 (29th January 2013) - Afrooz, Kambiz; Abdipour, Abdolali; Martin, Ferran
<x xml:space="preserve">Abstract</x> In this article, a set of differential equations to model the behavior of the extended composite right/left handed transmission line in time domain is proposed. These equations are solved by an explicit finite difference time domain algorithm. To investigate the numerical stability of the proposed algorithm, the amplification matrix is extracted. The results of the proposed algorithm are confirmed by the results of the Agilent ADS commercial software. © 2013 Wiley Periodicals, Inc. Int J RF and Microwave CAE 24:68–76, 2014.